2017
DOI: 10.3390/antiox6010015
|View full text |Cite
|
Sign up to set email alerts
|

Treating Cancer by Targeting Telomeres and Telomerase

Abstract: Telomerase is expressed in more than 85% of cancer cells. Tumor cells with metastatic potential may have a high telomerase activity, allowing cells to escape from the inhibition of cell proliferation due to shortened telomeres. Human telomerase primarily consists of two main components: hTERT, a catalytic subunit, and hTR, an RNA template whose sequence is complimentary to the telomeric 5′-dTTAGGG-3′ repeat. In humans, telomerase activity is typically restricted to renewing tissues, such as germ cells and stem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(83 citation statements)
references
References 84 publications
(159 reference statements)
2
75
0
1
Order By: Relevance
“…Telomeres and telomerase are key biological structures for supporting cancer cell proliferation since cancer cells can bypass the lifespan limits of normal cells by overexpressing telomerase (Telomerase +), or by using the alternative mechanism of telomere elongation (ALT+ cells). Hence, targeting telomeres or telomerase has been classically considered as a strategy for developing cancer therapies (7). In the present study, we have confirmed that TH5487 block BER initiation at telomeres in response to OS, and…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Telomeres and telomerase are key biological structures for supporting cancer cell proliferation since cancer cells can bypass the lifespan limits of normal cells by overexpressing telomerase (Telomerase +), or by using the alternative mechanism of telomere elongation (ALT+ cells). Hence, targeting telomeres or telomerase has been classically considered as a strategy for developing cancer therapies (7). In the present study, we have confirmed that TH5487 block BER initiation at telomeres in response to OS, and…”
Section: Discussionsupporting
confidence: 82%
“…Cancer cells are characterized by preserving stable telomere length, thereby conferring cell immortality (6). In consequence, the induction of telomeric instability is considered as a potential therapeutic strategy for cancer treatment (7).…”
mentioning
confidence: 99%
“…3 Then, telomerase inhibition has become a new potential therapeutic approach. 7,8 Telomerase activity is also associated with resistance to specific drugs, as Imatinib. 6 Whereas this enzyme is generally absent in normal cells and plays a crucial role in tumour ones, it is a good target for new drugs development.…”
Section: Introductionmentioning
confidence: 99%
“…6 Whereas this enzyme is generally absent in normal cells and plays a crucial role in tumour ones, it is a good target for new drugs development. 7,8 Telomerase activity is also associated with resistance to specific drugs, as Imatinib. 9 The anti-tumour potential of many telomerase inhibitors has been investigated, [10][11][12][13][14] but the effects of long-term treatment with these drugs on tumour cells remain not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…The paradigm that cancer cells are immortal was often linked with the statement that they proliferate indefinitely and avoid senescence due to active telomerase or alternative mechanisms of telomere lengthening [4]. For this reason, telomerase became a tempting target in experimental anti-cancer therapy [100]. The truth is, however, far more complex, which is evidenced by multiple observations that senescence may be triggered in cancer cells by their exposure to clinically relevant doses of ionizing radiation (radiotherapy) and chemotherapy [101].…”
Section: Therapy-induced Senescence Of Cancer Cellsmentioning
confidence: 99%